Pengaruh Atribut Produk Wisata terhadap Revisit Intention: (Studi Kasus pada Trans Studio Bandung) - Putri Hafsyari Ratulangie; Jihan fiqria; Abdul Yusuf (Lembaga Pengembangan Kinerja Dosen, 2025)
This research includes both quantitative descriptive research and a qualitative approach. To complement the qualitative data analysis, quantitative data is also used. The validity test results show a significance value below 0.05 and a Kaiser-Meyer-Olkin (KMO) value above 0.3. This confirms the validity of the data for the first variable as well as the questions pertaining to the second variable. The research employs Cronbach's Alpha technique with SPSS 26. An instrument is considered reliable if the reliability coefficient (r) > 0.6; thus, the data is valid as Cronbach's Alpha exceeds 0.6. This study aims to investigate the effect of tourism attributes at Trans Studio Bandung on visitors' intentions to return and to assess how these attributes influence their decision to revisit. Based on the findings and discussions previously outlined, it can be concluded that Trans Studio Bandung is a surprising tourist destination with numerous attractions. Destination attributes contribute to increasing revisit intentions, primarily among visitors aged 15 to 25, many of whom are students. The more tourism destination attributes that can be utilized, the more visitors are inclined to revisit Trans Studio Bandung. Visitor satisfaction indicates an intention to revisit, crucial for tourists to return to the same destination. Better tourism destination features at Trans Studio Bandung lead to greater visitor satisfaction, ultimately encouraging them to return.